Precursor B Cell Acute Lymphoblastic Leukemia Presenting with Repeated Episodes of Hemophagocytic Lymphohistiocytosis - Nihar Desai; Dinesh Chandra; Ruchi Gupta; Rajesh Kashyap (Indian Journal of Medical and Paediatric Oncology)
Hemophagocytic lymphohistiocytosis (HLH) is a rare disorder characterized by dysregulated activation of cytotoxic T-lymphocytes and macrophages, resulting in excessive cytokine release and tissue damage. Although hematological malignancies and the chemotherapies used to treat them are frequently identified as triggering factors for HLH, B lymphoid leukemias are rarely implicated. In this report, we present an interesting case of a patient who presented with symptoms of HLH and was subsequently diagnosed with B-cell acute lymphoblastic leukemia. The further course of chemotherapy was complicated by another episode of HLH. This case highlights the complexity and the diverse triggers of HLH in the context of B lymphoid leukemia. Recognizing this atypical presentation is important to institute timely management strategies.